2013
DOI: 10.1177/0895904813510777
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Effectiveness

Abstract: Historically, the government has sought to improve the quality of the teacher workforce by requiring certification. Teachers are among the most licensed public personnel employees in the United States. Traditionally, an education degree with a student teaching experience and passage of licensure exams were necessary for licensure. In the 1980s, alternative paths to certification developed. In this article, we evaluated the impact of licensure screens and licensure routes on student achievement. Our findings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Personal attributes (e.g., teachers’ background and experience) and characteristics of the preparation program such as coursework content, length, and intensity—notwithstanding the specific pathway—may be more important. A possible reason for this may be that, while ACTs have shorter preservice preparations relative to TCTs, associated feelings of self-doubt could be moderated by ACT differences in other key areas such as licensure exam scores (Shuls & Trivitt, 2015), age at time of initial certification (Redding & Smith, 2016), and the selectivity of the colleges and universities from which they graduate (Redding & Smith, 2016). Future study in music education is recommended to better understand whether these trends are similarly evident among ACMTs and TCMTs.…”
Section: Resultsmentioning
confidence: 99%
“…Personal attributes (e.g., teachers’ background and experience) and characteristics of the preparation program such as coursework content, length, and intensity—notwithstanding the specific pathway—may be more important. A possible reason for this may be that, while ACTs have shorter preservice preparations relative to TCTs, associated feelings of self-doubt could be moderated by ACT differences in other key areas such as licensure exam scores (Shuls & Trivitt, 2015), age at time of initial certification (Redding & Smith, 2016), and the selectivity of the colleges and universities from which they graduate (Redding & Smith, 2016). Future study in music education is recommended to better understand whether these trends are similarly evident among ACMTs and TCMTs.…”
Section: Resultsmentioning
confidence: 99%
“…The most apparent reason for states requiring preservice teacher testing is its positive relationship with teacher effectiveness. Shuls and Trivitt (2015) showed a positive correlation between teacher licensure exam performance and teacher efficacy and noted that alternatively certified teachers scored even higher than traditionally certified teachers. Because CTE is highly content-driven, many experts tend to devalue the importance of pedagogical skill and argue for expertise in the subject matter (Ballu & Podgurksy, 2000).…”
Section: Mandatory Testing and Cte Teacher Shortagementioning
confidence: 99%
“…Teachers with content-specific knowledge can support student learning and impact student math achievement (Hill & Lubienski, 2007;Shuls & Trivitt, 2015). Results from the study conducted by Shuls and Trivitt (2015) indicated content-specific knowledge, as demonstrated in teacher certification exams, significantly correlated with student achievement.…”
Section: Content-specific Knowledgementioning
confidence: 99%
“…Teachers with content-specific knowledge can support student learning and impact student math achievement (Hill & Lubienski, 2007;Shuls & Trivitt, 2015). Results from the study conducted by Shuls and Trivitt (2015) indicated content-specific knowledge, as demonstrated in teacher certification exams, significantly correlated with student achievement. Hill and Lubienski (2007) stated that "specialized knowledge of mathematics" includes the teacher's ability to determine the methods that are most beneficial for student learning when for example, representing mathematical procedures or solving computational problems.…”
Section: Content-specific Knowledgementioning
confidence: 99%
See 1 more Smart Citation